E0205 MicroRNA regulation of cardiomyocyte lineages from bone marrowderived mesenchymal stem cells. (17th November 2010) - Rongrong, Wu; Xiaozhou, Mo; Xinyang, Hu; Yaping, Wang; Chunsheng, Xiang; Jian-an, Wang
Abstract : Objective: ischaemic heart disease is the leading cause of morbidity and mortality all over the world. Cardiomyocytes from bone marrow-derived mesenchymal stem cells (MSCs) offer great potential for repairment of the infracted heart. However, this approach has been limited by inefficient differentiation of MSCs into cardiomyocytes. To overcome such a problem, the underlying regulation mechanisms for cardiac differentiation should be elucidated. MicroRNAs (miRNAs) are small noncoding RNAs of ∼23 nucleotides that control post-transcriptional gene expression. Recently, miRNA has been widely shown to regulate key cellular events such as cell proliferation, cell differentiation. The purpose of this study is to determine the role of miRNAs during cardiac differentiation from MSCs. Method: Firstly, we established a model of cardiac differentiation from rat bone marrow-derived MSCs using 10 μM 5-Aza, and performed a global miRNA analysis using EXIQON miRNA array to identify characteristic miRNA at different stage of differentiation. After being validated by real-time qRT-PCR and target gene prediction, several miRNAs such as miRNA-145 were further chosen to reveal its function during cardiac differentiation. Results: miRNA profiling revealed that miR-145 expression increased during cardiac differentiation, especially at 12 days of treatment (2.25-fold change vs untreated MSCs). Compared to other tissues such as liver, brain, kidney, miRNA-145 expression is highest in rat heart tissue. Gain-of-function methods using pre-miR-145 showed the enchancement of cardiac differentiation, confirmed by immunocytochemical staining with cardiac-specific myosin heavy chain antibody. Conclusion: miR-145 may be a critical regulator for cardiomyocyte lineage in our 5-Aza-induced differentiation system.